THE EFFECT OF DEEP BREATHING RELAXATION TECHNIQUES AND COLD COMPRESS TECHNIQUES ON PAIN LEVELS IN PATIENTS AFTER CRURAL FRACTURE SURGERY - Yunnita Setiyaningsih; Agusta Dian Ellina; Rahmania Ambarika (Universitas Nahdlatul Ulama Surabaya, 2025)
Background: Postoperative pain is a major complication following cruris fracture surgery. Non-pharmacological interventions such as deep breathing, relaxation, and cold compress therapy are widely used, but their comparative effects remain unclear. Objective: To compare the effectiveness of deep breathing relaxation and cold compress therapy in reducing postoperative pain among cruris fracture patients at Kustati Surakarta General Hospital. Methods: A quasi-experimental pretest–posttest two-group study involving 40 postoperative patients using total sampling. Pain was measured using the validated Numeric Rating Scale. Kruskal–Wallis and Wilcoxon tests were applied. Result: Both interventions significantly reduced pain levels (p < 0.05). Cold compress therapy demonstrated a greater decrease. Conclusion: Both interventions were associated with decreased postoperative pain, with cold compress therapy showing greater reduction. Further randomized studies are recommended.